2017
DOI: 10.1155/2017/3945403
|View full text |Cite
|
Sign up to set email alerts
|

Promising Therapeutic Strategies for Mesenchymal Stem Cell-Based Cardiovascular Regeneration: From Cell Priming to Tissue Engineering

Abstract: The primary cause of death among chronic diseases worldwide is ischemic cardiovascular diseases, such as stroke and myocardial infarction. Recent evidence indicates that adult stem cell therapies involving cardiovascular regeneration represent promising strategies to treat cardiovascular diseases. Owing to their immunomodulatory properties and vascular repair capabilities, mesenchymal stem cells (MSCs) are strong candidate therapeutic stem cells for use in cardiovascular regeneration. However, major limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 114 publications
0
33
0
Order By: Relevance
“…VEGF is an angiogenic and pro‐regenerative growth factor (Arsic et al, ). VEGF protects MSCs from cellular stress, supports myoblast growth, angiogenesis, and tissue regeneration (Ji, Kim, Yun, Chung, & Kwon, ). The expression of VEGF continuously increased over time after Day 5 (Figure ) suggesting the regenerative potential of MSCs also increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is an angiogenic and pro‐regenerative growth factor (Arsic et al, ). VEGF protects MSCs from cellular stress, supports myoblast growth, angiogenesis, and tissue regeneration (Ji, Kim, Yun, Chung, & Kwon, ). The expression of VEGF continuously increased over time after Day 5 (Figure ) suggesting the regenerative potential of MSCs also increased.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF protects MSCs from cellular stress, supports myoblast growth, angiogenesis, and tissue regeneration (Ji, Kim, Yun, Chung, & Kwon, 2017). The expression of VEGF continuously increased over time after MSCs are considered to be immunoprivileged and do not elicit an immune response in their new host (Ankrum, Ong, & Karp, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic heart damage disrupts this homeostatic balance, which leads to a series of cellular events including apoptosis, necrosis, various inflammatory responses, and remodeling processes resulting in scar formation, ventricular stiffness, and altered contractibility [ 3 ]. Though medical and surgical treatments such as pharmacotherapy, percutaneous coronary intervention (PCI), and surgical management can significantly improve patient outcomes and reverse viable ischemic tissue, no current treatment is able to create new contractile tissue or regenerate lost myocardium [ 4 ]. Heart transplantation is the only definitive treatment for the ischemic heart failure that results after MI; however, the procedure involves significant risk and donors are limited [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy to bolster the therapeutic potential of hMSCs is priming/preconditioning the hMSCs-which exposes them to physical treatments (e.g., hypoxia and heat shock), pharmacological agents, growth factors, distinct types of biomaterials, modified culture conditions, or other various molecules, including microRNAs-in vitro before transplantation into the hearts (11)(12)(13)(14)(15). Previous studies of the underlying mechanisms of the priming effects reported that hMSCs receiving these priming applications had short-term memory and remembered a priming stimulus, even after relocating to new environments, and shifted their phenotype in therapeutically desirable directions (14,16).…”
Section: Introductionmentioning
confidence: 99%